Life-course Social Position, Obesity and Diabetes Risk in the EPIC-Spain Cohort (2016)
ABSTRACT: Background: The literature has consistently shown that extreme social-economic groups predicted type 2 diabetes mellitus (T2D), rather than summarising the social gradient throughout all society stratification. Body mass index (BMI) was established as the principal mediator, with little support for other anthropometries. Our aim was to investigate an individual life-course social position (LiSoP) gradient and its mediators with T2D risk in the EPICSpain cohort. Methods: 36 296 participants (62% women), mostly aged 30–65 years, and free of T2D at baseline (1992–1996) were followed up for a mean of 12.1 years. A combined score of paternal occupation in childhood and own adult education assessed individual life-course social risk accumulation. Hazard ratios of T2D were estimated using Cox regression, stratifying by centre and age, and adjusting for different explanatory models, including anthropometric indices; dietary history; smoking and physical activity lifestyles; and clinical information. Results: Final models evidenced significant risks in excess of 63% for middle and 90% for lower classes of LiSoP in men; and of 104 and 126%, respectively, in women. Concurrently, LiSoP presented significant social gradients for T2D risk (P < 0.01) in both sexes. Waist circumference (WC) accounted for most of the risk excess in women, and BMI and WC in men. Conclusions: LiSoP gradient was related to T2D risk in Spanish men and women. WC mostly explained the relationship in both genders, together with BMI in men, yet LiSoP retained an independent effect in final models.